Konsep Pengasuhan Positif Berdasarkan Falsafah Sapa Sira Sapa Ingsun Sebagai Solusi Toxic Parenting - A’ida Fayza Fitrianetha; Dhita Adsa Adani; Mujahidah Shaksiyyatul Karimah; Aulia Nuurin Mahfudloh; Mohamad Abrar Putera Radian; Bani Bacan Hacantya Yudanagara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Indonesian Central Statistics Agency reports that 30.2 million children require adequate social, economic, and educational protection, yet toxic parenting systems often become the main obstacle. The high prevalence of child abuse indicates the need for positive and culturally-based parenting approaches. This study aims to explore and test the Sapa Sira Sapa Ingsun philosophy as a positive parenting approach to address toxic parenting. The first study involved in-depth interviews with figures from the Surakarta Palace, revealing parenting principles such as the balance between intellectual, spiritual, and emotional intelligence, and two-way communication. The second study confirmed these findings through the opinions of parenting experts. The third study, a psychodrama experiment with 34 parents, demonstrated that positive parenting based on the Sapa Sira Sapa Ingsun philosophy is effective in reducing toxic parenting. Paired samples t-test results showed a significant difference between pre-test and post-test scores, with t(33) = 9.84 and p < 0.001. The effect size calculated using Cohen's d was 1.69, indicating a very large effect of the intervention. This shows a statistically significant difference between pre-test and post-test scores, suggesting a meaningful change after the intervention. In conclusion, the Sapa Sira Sapa Ingsun philosophy can be widely applied as a positive parenting solution to overcome toxic parenting.